Digitizing Zakat Collection through the E-payment System - Angga Syahputra; Mukhtasar Mukhtasar (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2021)
This country has enormous zakat potential, the figure reaching 330 trillion per year. However, the realization is still far from what is expected and does not even reach 5% of the existing potential. Zakat is a financial instrument in Islam that is able to break the chain of poverty and distribute wealth properly. Zakat is able to provide positive significance in economic growth and elevate human dignity. The large population and wide area of Indonesia, apart from being a potential, also have obstacles in collecting zakat, which has been done using conventional methods. For this reason, researchers conducted research on the extent to which digitization of zakat collection through the e-payment system has played a role so far. The method used in this research is a qualitative research method with the type of library research and secondary data sources obtained from journals, books, previous research and websites that have good credibility. The results of this study describe a significant increase in zakat funds collected through electronic zakat payments. The e-payment system in collecting zakat has been proven to provide comfort, security, flexibility in time and place, efficiency, and is effective for muzakki in distributing zakat payments